Evaluation to tomato bacterial spot in different spray regimes - Marcuzzo, Leandro Luiz; Fernandes, José Mauricio Cunha; Becker, Walter Ferreira (Revista de Ciências Agroveterinárias, 2015)
The control of tomato bacterial spot was carried out based on chemical spraying on a fixed schedule, without considering the progress of the disease. The spraying system based on a mathematical model can predict this progress and also reduce the number of sprays and maximize the disease control. Spraying regimes were established according to estimated severity of 0.05, 0.15, and 0.25 according to a previous published forecast model and compared with standard regimes with chemical applications at intervals of 5 and 7 days. In order to evaluate different spraying regimes on tomato bacterial leaf spot severity, the statistical modeling technique known as mixed models was applied. These models not only include fixed effects but also random effects to each one of the individuals of the population under study. Cumulative bacterial spot severity as a function of weeks after transplanting for five spraying regimes was calibrated to a Logistic model where the fit was obtained for the mixed model where a random effect was adjusted to the upper asymptote. This parameter represents the potential disease severity for each one of the treatments. As a result of model calibration, the treatment with the lowest disease severity was the one sprayed with estimated severity of 0.05 with 36 sprays of fungicide with bactericide action. However, the treatment with disease severity of 0.15 resulted in reduced disease severity of 26.28%.